2011
DOI: 10.1111/j.1365-2702.2011.03696.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational social class, coping responses and infertility‐related stress of women undergoing infertility treatment

Abstract: Nurses and midwives who work in infertility clinics should aim to identify individuals who are at high risk for infertility stress and adjustment difficulties and they should minimise the identified risk factors for infertility-related stress and strengthen the protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
(54 reference statements)
2
25
1
2
Order By: Relevance
“…In particular, many of them avoided interactions with those expecting a baby or who had children [9,42]. It is an important finding for the professionals working in the field, that all women from all the stress levels groups in our study displayed social withdrawal, which is a drawback for women while trying to overcome and adjust to infertility [11,13,42,43]. Clinic nurses must not rule out the fact that women displaying "social withdrawal" are at risk of high stress levels.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, many of them avoided interactions with those expecting a baby or who had children [9,42]. It is an important finding for the professionals working in the field, that all women from all the stress levels groups in our study displayed social withdrawal, which is a drawback for women while trying to overcome and adjust to infertility [11,13,42,43]. Clinic nurses must not rule out the fact that women displaying "social withdrawal" are at risk of high stress levels.…”
Section: Discussionmentioning
confidence: 96%
“…They add no significant difference was found with other variables such as age, education, occupation, religion, family income and duration of infertility in years. Lykeridou K (2011) (39) also reported that there was no significance association between age, medical characteristics and coping strategies.…”
Section: Coping Strategies and Quality Of Life Among Infertile Women mentioning
confidence: 99%
“…First, Vinitha D et al (2015) (38) who suggested that there is no significant difference between coping strategies used by the infertile women and their level of education. Second, Lykeridou K et al (2011) (39) who reported that women of low education used higher levels of active-confronting coping than women of high education (F = 7.997, P < 0.001). They also added that women of low education used passive avoidance coping more than women of high education.…”
Section: Coping Strategies and Quality Of Life Among Infertile Women mentioning
confidence: 99%
“…An under-explored aspect of infertility investigations and treatments is the effect of social class, race/ethnicity and religion (Latifnejad Roudsari & Allan, 2011;Lykeridou et al, 2011).…”
Section: Anxietymentioning
confidence: 99%